The natural unnaturalness of real-time narrative: The complex case of the sporting radio broadcast. (2nd June 2012) - Watson, Cate
In this article I draw on the contested concepts of naturalness and unnaturalness in narrative, in order to analyse the sporting radio broadcast. I take as my case the ball-by-ball broadcasting of cricket on the BBC radio programme Test Match Special, examining its complexity in narrative terms and uncovering its 'unnatural' elements. The aim of this analysis is to reveal the complexity of the sporting radio broadcast, exposing it as a fictional narrative, and furthermore a most unnatural one at that. In doing this I draw on work by Jan Alber and colleagues (2010), who present an analysis of 'unnatural narratives' defined in terms of logical and/or physical impossibilities in three interconnected areas: unnatural storyworlds; unnatural minds; and unnatural acts of narration. The purpose of this is to exploit the uncertainty inherent in the unstable natural/unnatural dichotomy in order to produce a different reading, thereby enabling new insights to be generated.